Targeting the D1-N-methyl-D-aspartate receptor complex reduces L-dopa-induced dyskinesia in 6-hydroxydopamine-lesioned Parkinson’s rats - Song L; Zhang ZZ; Hu RG; Cheng J; Li L; Fan QY; Wu N; Gan J; Zhou MZ; Liu ZG (Dove Medical Press, 2016)
Lu Song,1,* Zhanzhao Zhang,2,* Rongguo Hu,1 Jie Cheng,1 Lin Li,1 Qinyi Fan,1 Na Wu,1 Jing Gan,1 Mingzhu Zhou,1 Zhenguo Liu11Department of Neurology, Xinhua Hospital, 2Department of Plastic and Reconstructive Surgery, Shanghai 9th People’s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China*These authors contributed equally to this workAbstract: L-3,4-dihydroxyphenylalanine (L-dopa) remains the most effective therapy for Parkinson’s disease (PD), but its long-term administration is associated with the development of debilitating motor complications known as L-dopa-induced dyskinesia (LID). Enhanced function of dopamine D1 receptor (D1R) and N-methyl-d-aspartate receptor (NMDAR) is believed to participate in the pathogenesis of LID. Given the existence of physical and functional interactions between D1R and NMDAR, we explored the effects of uncoupling D1R and NMDA GluN1 (GluN1) interaction on LID by using the Tat-conjugated interfering peptide (Tat-D1-t2). In this study, we demonstrated in 6-hydroxydopamine (6-OHDA)-lesioned PD rat model that intrastriatal injection of Tat-D1-t2 alleviated dyskinetic behaviors and downregulated the phosphorylation of DARPP-32 at Thr34 induced by levodopa. Moreover, we also showed intrastriatal administration of Tat-D1-t2 elicited alterations in membranous GluN1 and D1R expression. These findings indicate that D1R/GluN1 complexes may be a molecular target with therapeutic potential for the treatment of dyskinesia in Parkinson’s patients.Keywords: 6-hydroxydopamine, Parkinson’s disease, dyskinesia, L-dopa, D1 receptor, NMDA, protein–protein interaction